Clinical and hemodynamic benefit of macitentan and riociguat upfront combination in patients with pulmonary arterial hypertension. (1st February 2019) - Sulica, Roxana; Sangli, Swathi; Chakravarti, Aloke; Steiger, David
Abstract : In this open‐label study, we evaluated the effect of upfront macitentan and riociguat combination in newly diagnosed pulmonary arterial hypertension (PAH) patients. In 15 consecutive PAH patients, we collected clinical and hemodynamic data at baseline, visit 1 (median 4 months) and visit 2 (median 12 months). Survival and transplantation status were analyzed over 36 months. Statistical analysis included student t ‐test and 95% confidence interval (CI) ( t ‐statistic or Clopper‐Pearson). Kaplan‐Meier was used to estimate survival rate. There were 11/15 women (mean age 56 years), in World Health Organization (WHO) functional class (FC) III ( n = 14) or IV ( n = 1). The 6 min walk distance increased from 281.6 m (baseline) to 315.7 m (visit 1) and visit 2 (313.9 m), representing a 34‐ and 32‐m change ( P < 0.05), respectively, associated with Borg score improvements. Brain natriuretic peptide decreased: 318.2 pg/mL (baseline) to 122.0 pg/mL (visit 1) and 98.6 pg/mL (visit 2) ( P < 0.05). WHO FC improved in eight patients (53%, 95% CI 27%–79%). Pulmonary vascular resistance (9.2 to 5.7 Wood Units) and mean pulmonary artery pressure (47.3 to 38.9 mmHg) decreased; cardiac index increased (2.3 to 3.0 L/min/m 2 ) (baseline to visit 2, all P < 0.05). All patients had intermediate and high risk score (baseline); at 1‐year follow‐up, dual therapy led to reduction to low risk score in 7/15 (47%) patients. There were no unexpected or serious side effects. Three patients died due to unrelated causes; one patient received a lung transplant. Transplant‐free survival rate (36 months) was 85%. Preliminary evidence is provided for effectiveness of initial macitentan and riociguat combination therapy in PAH.